PO263 Moyamoya disorder a north-west england experience. (1st December 2017) - Rajashekar, D; Williamson, J; Nahser, H; Bhojak, M; Sekhar, A; Enevoldsen, TP; Sinha, AK; Malluci, C; Visca, A; Menon, RK
Abstract : Background: Moyamoya disorder is a progressive intracranial cerebrovascular disease of unknown aetiology. The Walton Centre is a tertiary neuroscience centre serving a population of 3.5 million, Alder Hey Children's Hospital is a tertiary paediatric hospital. Aim: To compare stroke type, radiological features and clinical outcome in paediatric and adult population with Moyamoya disorder. Methodology: Retrospective case note review of patients diagnosed with Moyamoya disorder at both sites from January 2007 to December 2016. Results: 27 adults and 9 paediatric patients were identified. 5 of the adult patients presented during childhood. Mean age of presentation was 39 in the adult cohort and 7 in the paediatric cohort. Female to male ratio was 2:1. A majority were Caucasian. The commonest presentation in both groups was ischaemic stroke. Unilateral radiological features were seen in a majority of adult patients compared to bilateral features in paediatric cohort. 11 of the patients were managed surgically with procedures including EC-IC bypass and encephaloduroarteriosynangiosis. Conclusion: This study demonstrated that a majority adult cohort had ischaemic stroke with unilateral radiological features and majority paediatric population had bilateral moyamoya disease. We conclude that the primary pathogenesis is likely to be different in the adult and paediatric population.